Robot-assisted donor hysterectomy in uterus transplantation - a modality to increase reproducibility - Chmel, Roman; Pastor, Zlatko; Novackova, Marta; Chmel, Roman (Ginekologia polska, 2021)
Uterus transplantation is a non-lifesaving vascularized composite allotransplantation procedure requiring immunosuppression until removal of the graft. The focus of uterus transplantation is changing regarding refining individual treatment procedures included in this complex treatment of absolute uterine factor infertility, such as robot-assisted donor hysterectomy. The inferior hypogastric nerve plexus should be preserved during robotic dissection of the ureter and uterine vessels to prevent postoperative complications such as urine and fecal evacuation disturbances and sexual disorders. As most uterus transplantations have been performed in living donor concepts, robot-assisted donor hysterectomy should contribute to increased availability of uterus transplantation, particularly because it uses the precise blood-less technique of surgical dissection in the deep pelvis and has cosmetic benefits among living donors.
Keywords: robot-assisted surgery; Robotics; Humans; Pelvis; living donor; pánev; reprodukovatelnost výsledků; Uterus; transplantation; hysterectomy; robotika; uterus; hysterektomie; Robotic Surgical Procedures; ženské pohlaví; lidé; roboticky asistované výkony; Reproducibility of Results; Hysterectomy; Female